Analysis of Engine Efficiency of Diesel Vehicle in Transient Operating Conditions - Chung, In Chun; An, Young Kuk; Park, Jinil; Lee, Jonghwa; Ji, Yohan (International Journal of Automotive Technology, 2021)
The main objectives of engine development, given the increased environmental regulations, are performance and efficiency improvement, and emission reduction. Notably, for diesel engines, the significance of fuel consumption and emission reduction is increasing because they emit harmful materials (PM, NOx); however, they are characterized by relatively low CO2 emission in comparison with gasoline engines. Various technologies have been developed to solve these problems of diesel engines; however, majority of the diesel engines are developed in a steady state, and yet their certification and evaluation include the transient state. The transient operation of diesel vehicles leads to additional fuel consumption and emission of NOx; however, the impact of transient operation has not been discussed thus far. Therefore, this study quantitively investigates the fuel consumption and NOx emission during the transient operation of a diesel vehicle. First, the engine and vehicle’s efficiency and NOx emission differences are derived and analyzed in the steady state. Subsequently, the effects of the vehicle’s transient operation are analyzed. A vehicle’s transient operation can be classified into two types: operational and thermal transient effects. Finally, the respective transient effects are quantified and analyzed.
Keywords: Efficiency improvement; Emission reduction; Engine development; Engine efficiency; Thermal transient effect; Transient operating condition; Transient operation; Various technologies; Diesel engine; Energy flow down; Fuel consumption; NOx emission; Thermal transient; Transient operation